Knowledge, attitude, and awareness toward orthodontic treatment among patients: A questionnaire survey - T Sarva Sri; Nivethigaa Balakrishnan; Swapna Sreenivasagan; B Nivethigaa (Wolters Kluwer Medknow Publications, 2022)
The current study's objective is to learn more about how patients, depending on their gender, perceive, feel, and know about orthodontic therapy.There was a cross-sectional survey among 100 patients to evaluate their knowledge and attitude toward orthodontic treatment. The questionnaire was prepared and circulated among patients using online google forms. The online responses were collected and tabulation of the data was done in excel sheets. Data was analysed using statistical software. Chi square test to compare the association of gender and patients knowledge regarding orthodontic treatment. In the current study 53% of the study population had visited an orthodontist. 79.6% of the patients are conscious that their teeth can be aligned properly by an orthodontist. 73.5% think that teeth should be properly positioned for a better facial appearance. According to the findings in the present study, it is evident that there is awareness and understanding regarding the orthodontic treatment among patients.